Monitoring 5G Backhaul: An In-Band Telemetry Approach for Quality of Service - Eurico Dias; Duarte Raposo; Miguel Luis; Pedro Rito; Susana Sargento (IEEE Access)
The use of Ultra-Dense Networks within 5G communications can be leveraged by the adoption of Millimeter-Wave (mmWave) technology for the backhaul, resulting in cost reductions and faster deployment of the infrastructure. However, this shift also introduces new concerns and restrictions. The wireless link susceptibility to signal strength and link loss degradation, due to loss of line-of-sight, makes the link quality inconsistent. The heterogeneity of network nodes poses an additional challenge for tracking link quality changes reliably. An effective network monitoring system using 5G Quality of Service (QoS) Indicators is necessary to correctly characterize and track channel and flow quality conditions in a 5G wireless backhaul. To tackle these challenges, we introduce an In-Band Telemetry (INT) approach, consisting of a P4-compatible dataplane model and an aggregation agent capable of gathering and processing per-packet measurements, exposing them as link and QoS flow quality metrics, suitable for integration with Software Defined Network (SDN) environments and 5G networks. Our study compares the accuracy achieved by the proposed in-band solution to a commercial network management system, in an outdoor test-bed with an obstructed mmWave backhaul link. The results demonstrate that this approach exhibits minimal measurement errors when assessing the throughput, latency, and Packet Error Rate (PER) of mmWave links. The solution attains an average forwarding overhead of approximately 17%, while maintaining a per-node aggregation processing total time upper-bound of 45 ms at 2.5 Gbps line rate.